Can the recurrence rate of open pilonidal sinus surgery be reduced by preventing premature epithelialization - Izzat Bihnam Muttosh (Advanced Medical Journal)
Background and objective: Many surgical options are known to treat chronic pilonidal sinus disease; the procedure that has the least recurrence rate is the open method. This study aimed to evaluate the effect of adding one step in management, on the recurrence rate of the same procedure.